Transplant2Mongo: Python Scripts that Insert Organ Procurement and Transplantation Network (OPTN) Data in MongoDB - Harvey, Christine; Weigel, R. S. (Journal of open research software, 2019)
transplant2mongo allows users to transform Standard Transplant Analysis and Research (STAR) ASCII data files from the Organ Procurement and Transplantation Network (OPTN) into a MongoDB database [1, 2]. The STAR data are a complex collection of tab-separated files with inter-related records that are not amenable to complex queries. A researcher planning to use OPTN STAR data can use transplant2mongo to convert the data into a MongoDB database and then use open-source tool software for analysis. The source code for transplant2mongo is available on GitHub at https://github.com/ceharvs/transplant2mongo and includes sample data files for initial testing and queries.   Funding Statement: The software referenced herein is copyright of The MITRE Corporation and the result of MITRE’s Early Career Research program and work done in the Computational Science and Informatics program at George Mason University. Approved for Public Release; Distribution Unlimited. Case Number 18-0298. The author’s affiliation with The MITRE Corporation is provided for identification purposes only and is not intended to convey or imply MITRE’s concurrence with, or support for, the positions, opinions, or viewpoints expressed by the author.